The Effect of Biochar and Nitrogen Doses on Yield and Mineral Concentrations in Peanut - Zeliha KÜÇÜKYUMUK (ISPEC Journal of Agricultural Sciences)
In this study, effect of biochar and nitrogen doses on the yield of peanut plants and the nutrient element contents of leaves were investigated. For this purpose, 2 tons da-1 biochar and biochar + nitrogen applications were grown during the vegetation period. The fruit weights of the harvested plants and the N, P, K, Ca, Mg, Fe, Zn, Cu, Mn, and B concentrations of peanut leaves were determined. As a result of the research, the highest fruit weight nitrogen and the highest N concentration were determined in the biochar + 10 kg da-1 N application. According to the results, there was a 5% decrease in fertilizer requirement as a result of the application of biochar to the soil in peanut plants. The effect of the applications increased the Ca, Mn, and Cu concentrations while decreasing the P, K, Mg Fe, Zn concentrations. The effects of the applications on B concentrations were different. As a result of this research, it is possible to say that mixing biochar and nitrogen will be an effective method for more effective use.